PENGEMBANGAN WISATA DALAM RANGKA MENINGKATKAN PENDAPATAN ASLI DAERAH KABUPATEN BREBES - Medi Tri Purwanto (Jurnal Strategik, 2020)
AbstrakThe tourism development in Brebes Regency is more inclined to the development  of  natural  tourism  areas  such  as  the  Ranto  canyon  waterfall,  the princess waterfall, Kaliwlingi mangrove forest and the Pany Host waterfall. The development is carried out in an effort to improve the quality of these tourist attractions.  Where,  the  development  carried  out  by  the  local  government  is  to improve the infrastructure in tourist areas, such as repairing good roads. This is done because the tourism is an asset owned by the regency of Brebes Regency.